All-Inside Arthroscopic Tie-Grip Suture Repair for Radial Tear in the Midbody of Lateral Meniscus Using an All-Inside Device and Slotted Cannula - Masaki Iguchi, M.D.; Tsuneari Takahashi, M.D., Ph.D.; Mikiko Handa, M.D.; Katsushi Takeshita, M.D., Ph.D. (Arthroscopy Techniques)
Inside-out repair of meniscal tears is the gold standard surgical approach; however, its use is limited by the need for a posterior incision and neurovascular risk. In this Technical Report, we present details of the all-inside arthroscopic tie-grip approach for repairing a radial tear of the midbody of the lateral meniscus using an all-inside device (TRUESPAN) and a slotted cannula. In contrast to the inside-out approach, this technique helps reduce surgical invasiveness and provides stable fixation as the vertical mattress sutures bundle the circumferential fibers and act as rip stops for the horizontal sutures. However, the operating surgeon must understand proper insertion techniques to successfully use the devices required for this procedure.